Pengaruh Karakteristik Usaha dan Akses LKM Terhadap Omzet Pedagang Mikro Perempuan Salatiga - Manullang, Tya Anastasya; Thenu, Tirsa Natasha; Sundari, Sundari; Saraswati, Birgitta Dian (MDP Student Conference, 2025)
This study evaluates the impact of access to Microfinance Institutions (MFIs) on the development of women-owned micro-enterprises in Salatiga City. Using a quantitative approach and multiple regression analysis, the study involved 90 female micro-entrepreneurs. The variables examined include education level, business competition, ownership status, business age, and MFI access in relation to business revenue. The findings reveal that education level significantly influences revenue, while other variables show no significant impact. Most entrepreneurs rely on self-funding (61%), with only 28% utilizing MFI loans, influenced by high borrowing costs and complex procedures. This study highlights the need for more inclusive financial access and empowerment strategies for female entrepreneurs to support the sustainable growth of micro-enterprises.